(untitled) (International Journal of Engineering and Computer Science, 2014)
The Cloud computing is a general term used to describe a new class of network based computing that take place over the internet. These platform hide the complexity and details of underlying infrastructure from users and applications by providing very simple graphical interface. Basically, clouds are of three categories. IT organizations can choose to deploy applications on public, private, or hybrid clouds. In this paper we are studding Private and Public Cloud